2021
DOI: 10.1177/11206721211006583
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent keratoconjunctivitis as the sole manifestation of COVID-19 infection: A case report

Abstract: Introduction: Ocular symptoms are uncommon manifestations of coronavirus disease 2019 (COVID-19) infection. Earlier study reported that dry eye, blurred vision, foreign body sensation, tearing, itching, conjunctival secretion, conjunctival congestion, ocular pain, and photophobia are among the ocular symptoms that could be found in COVID-19 patients. However, there are only a few reports available regarding corneal involvement in this disease. Here we report a case of keratoconjunctivitis as the only symptom o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Conjunctivitis 2 , 10 , 11 and keratoconjunctivitis 12 are the most prevalent ocular symptoms in adults. 13 Conjunctival irritation was the most prevalent ophthalmological finding (50.8%), followed by diplopia (27.8%) and cotton wool patches (27.8%).…”
mentioning
confidence: 99%
“…Conjunctivitis 2 , 10 , 11 and keratoconjunctivitis 12 are the most prevalent ocular symptoms in adults. 13 Conjunctival irritation was the most prevalent ophthalmological finding (50.8%), followed by diplopia (27.8%) and cotton wool patches (27.8%).…”
mentioning
confidence: 99%
“…Corneal manifestations in SARS-CoV-2 infections are rare. They are mainly cases of superficial punctate keratitis [28,29]. Subepithelial inflammatory tree-like keratitis similar to that seen in herpetic keratitis has also been described [22].…”
Section: Anterior Ocular Segment Manifestations Of Sars-cov-2 Infectionmentioning
confidence: 93%
“…In addition to conjunctivitis, ocular surface manifestations of COVID-19 described in the literature also include keratitis [22,28,29] and scleritis [30,31].…”
Section: Anterior Ocular Segment Manifestations Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Serous conjunctivitis is the most common ocular manifestation in patients with COVID-19, and its prevalence has been reported to range from 0.8% [33] to as high as 64% [34]. Most authors reported the incidence of ocular symptoms between 3% and 8%, and interestingly, investigators have reported a much lower incidence of keratitis than conjunctivitis [35][36][37]. In a study conducted on a group of 74 patients, Polish authors demonstrated the presence of ocular symptoms in almost half of the subjects (n = 35), but only 7 patients showed advanced conjunctivitis [36].…”
Section: Ocular Manifestations In Sars-cov-2 Infectionmentioning
confidence: 99%